1987
DOI: 10.1159/000275955
|View full text |Cite
|
Sign up to set email alerts
|

Immune Complexes and Complement Components in Bell’s Palsy

Abstract: The serum levels of circulating immune complexes were studied in 63 patients and the complement system in 36 patients with Bell’s palsy. The IgG-Clq and IgG-C3 containing immune complexes were analyzed by an enzyme-linked immunosorbent assay. The levels were found to be significantly elevated in the acute and convalescent stages of the palsy compared with controls. The total complement activity as determined by a CH50 assay and complement component C3 titrations also showed elevated values. The leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
(22 reference statements)
2
6
0
Order By: Relevance
“…We have previously reported on in creased levels of Clq-and C3-containing cir culating immune complexes in Bell's palsy [5]. The analysis in the present study of these patients' sera, with a similar method, re vealed slightly decreased levels of C4-containing circulating immune complexes.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…We have previously reported on in creased levels of Clq-and C3-containing cir culating immune complexes in Bell's palsy [5]. The analysis in the present study of these patients' sera, with a similar method, re vealed slightly decreased levels of C4-containing circulating immune complexes.…”
Section: Discussionsupporting
confidence: 69%
“…An infectious cause associated with an autoimmune response may be in volved in the disease [1,2], This is in agree ment with the finding of a prolonged immu nological response during the course of the disease [3]. In accordance with an immuno logical dysfunction, elevated serum levels of complement component Clq-and comple ment component C3-containing circulating immune complexes have been reported in the acute stage of Bell's palsy [4,5].…”
Section: Introductionsupporting
confidence: 68%
“…Other immuno¬ logìe abnormalities in this syndrome include elevated levels of circulating immune complexes and depression of the circulating cells.20·21 Similar immunologie changes have also been reported to occur in patients with Bell's palsy. [22][23][24][25][26][27] Increased antiviral activity in the serum of patients with multiple scle¬ rosis has been reported. 28 However, there are conflicting results and, accordingly, negative findings with the absence of IFN2' and IFN-730 in the serum of patients with multiple sclerosis have been reported.…”
Section: Commentmentioning
confidence: 99%
“…These reports were supported by animal studies demonstrating facial paralysis following injection of herpes simplex virus into the surface of the nerve 12 . Still other clinical reports suggested that Bell's palsy may be an autoimmune polyneuritis which followed a viral infection 13 . Adour noted that patients with this condition frequently demonstrated involvement of other cranial nerves such as the 9th, 10th, 11th, and the 8th cranial nerves 14 .…”
mentioning
confidence: 89%